ANALISIS RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2013 - Aryani Intan Endah Rahmawati; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
The economic crisis in 2008 was sourced from the United States continued in othercountries that lead the global economic crisis. This has an impact on the economy in Indonesia because Indonesia is a small open economy and very sensitive to external factors. Manufacturing company is one of the companies which experienced a decline in production. Companies that continue to show declining performance is feared will experience financial distress that led to the bankruptcy of the company. Elloumi and Gueyie defines financial distress as a company that has earnings per share (earnings per share) negative. Financial distress is important to learn because it serves as a sign that a company will go bankrupt in order to take anticipatory action to prevent it. This research aims to test the effect of financial ratios to financial distress at a manufacturing company listed on Indonesia Stock Exchange (IDX) in period 2008-2013. The results showed that only the ratio of earnings before interest and tax to total asset that affect both financial distress on one or two years before financial distress. However,other factors, such working capital to total asset, market value of equity to book value of total liabilities, retained earnings to total asset, sales to total asset, and cash flow from operations to total asset do not affect both financial distress on one or two years before financial distress.